Training Michael Phelps - Bowman, B.; Stott, M. J. (Swimming Technique, 2003)
The main component of Michael Phelps' phenomenal success besides his "made-for-swimming" physique is the carefully-crafted training program. Bob Bowman, the 2001 ASCA Coach of the Year, explains his training philosophy for Michael Phelps and provides sample workouts.